Supply Chain Analysis to Support the Welfare of Fishermen and Fish Farmers in East Kalimantan - Nugroho, Bramantyo Adi; Raharjo, Sugeng; Auliansyah, Auliansyah; Aprianti, Yesi; Fitriansyah, Fitriansyah; Putra Noor, Andy Dharma (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2026)
This study aims to examine the structure, model, actors, resources, business processes, and performance of the fisheries commodity supply chain in East Kalimantan and to identify an appropriate supply chain model to optimize the income and welfare of fishermen and fish farmers. An explanatory sequential mixed-methods approach was employed over six months across Kutai Kartanegara, Berau, North Penajam Paser, Balikpapan, Samarinda, and Bontang. The findings indicate that capture fisheries and aquaculture contribute substantially to regional fisheries production, with aquaculture showing the most significant annual growth, supported by government assistance through the provision of high-quality fish seed. Kutai Kartanegara and Balikpapan remain the leading contributors to the fisheries sector. Despite increasing production, distribution efficiency remains suboptimal. Patron–client relationships between fishermen and collectors create asymmetric market power, limiting fishermen's bargaining position and preventing them from determining fair prices, thereby constraining their welfare. Strengthening fishermen's human capital and entrepreneurial capacity is essential to increase value addition through fish processing and product diversification, enabling higher incomes. The study recommends improving fisheries supply chain infrastructure and logistics while enhancing transparency in market information systems to create a more efficient, equitable, and sustainable fisheries supply chain.